Don Quixote in His Labyrinth: Carnivalesque Folly, Lust, and Chaos at the Inn. - Horacio Chiong Rivero (Neophilologus, 2008)
Cervantes, already anticipating Borges, is the great inventor of labyrinths in Hispanic literature. In the intricately labyrinthine space that Juan Palomeque’s inn encloses, myriad interlaced narrative threads converge. Many are the diverse narrative stories that, by a seemingly providential stroke of good luck, happen to gravitate precipitously toward the very center of the labyrinth that the inn represents. The inn, therefore, emerges as a highly emblematic narrative frame, a “confusing labyrinth,” as the narrator calls it, a space that encapsulates an entire world of carnivalesque follies and a topsy-turvy world of misadventures, chaos, and chance encounters. The labyrinth, which serves as both a literary motif and as an aesthetic frame, seems to have a dual function in the forging of the first modern novel: it not only exemplifies Don Quixote’s seemingly endless quest for fiction, for the invention and discovery of multiple adventures, but it also offers a coherent and cohesive structural frame to a finely wrought and complex novel that is composed of an intricate web of interlaced episodes and interwoven narrative threads.